2001
DOI: 10.1016/s0002-9440(10)61711-7
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of the ALK Gene to the Clathrin Heavy Chain Gene, CLTC, in Inflammatory Myofibroblastic Tumor

Abstract: Inflammatory myofibroblastic tumor (IMT) is a rare, but distinctive mesenchymal neoplasm composed of fascicles of bland myofibroblasts admixed with a prominent inflammatory component. Genetic studies of IMTs have demonstrated chromosomal abnormalities of 2p23 and rearrangement of the anaplastic lymphoma kinase (ALK) gene locus. In a subset of IMTs, the ALK C-terminal kinase domain is fused with a tropomyosin N-terminal coiled-coil domain. In the current study, fusion of ALK with the clathrin heavy chain (CTLC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
178
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(183 citation statements)
references
References 18 publications
2
178
0
3
Order By: Relevance
“…11 Subsequently, recurrent ALK chimeric oncogenes involving diverse partner genes (RanBP2, CLTC, CARS, and others) were identified in inflammatory myofibroblastic tumors. [15][16][17][18] More recently, the ALK gene has been shown to be involved in small subsets of epithelial malignancies, including carcinomas of pulmonary, esophageal, mammary gland, and gastrointestinal origin. [19][20][21][22] To the best of our knowledge, this is the first report of a recurrent ALK locus rearrangement in a primary kidney tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Subsequently, recurrent ALK chimeric oncogenes involving diverse partner genes (RanBP2, CLTC, CARS, and others) were identified in inflammatory myofibroblastic tumors. [15][16][17][18] More recently, the ALK gene has been shown to be involved in small subsets of epithelial malignancies, including carcinomas of pulmonary, esophageal, mammary gland, and gastrointestinal origin. [19][20][21][22] To the best of our knowledge, this is the first report of a recurrent ALK locus rearrangement in a primary kidney tumor.…”
Section: Discussionmentioning
confidence: 99%
“…This probe set was used to confirm or assess for the presence of a VCL-ALK fusion in cases 1 and 2, respectively, and to further characterize the cytogenetically complex chromosomal rearrangements observed in case 1. Whole chromosome paint and centromere-specific probes for chromosomes 9 and 10 (Cytocell, Cambridge, UK and Abbott 16 Hybridization signals were assessed in 1-3 metaphase cells for each FISH probe combination (case 1) or in 200 interphase nuclei (cases 1-6); strong, well-delineated signals were independently scored by two individuals. An interphase cell specimen was interpreted as abnormal if split ALK break-apart probe signals were detected in 45% of the cells or juxtaposed VCL-ALK probe set signals were detected in 410% of cells (42 s.d.…”
Section: Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,7,9,[20][21][22][23][24][25][29][30][31][32] Cytogenetic and molecular analyses have demonstrated a number of ALK fusion gene partners, including RANBP2-ALK, TPM3-ALK, TPM4-ALK, CLTCALK, CARS-ALK and SEC31L1-ALK. 5,9,21,25,29,31 In the present study, ALK rearrangements were identified in 14 of 21 cases of inflammatory myofibroblastic tumor of the urinary bladder. These findings are similar to recent studies that identified ALK rearrangements by FISH in a few series of urinary bladder inflammatory myofibroblastic tumors.…”
Section: Utility Of Alk-1 Protein Expressionmentioning
confidence: 99%
“…[20][21][22] The favourable outcome of IMFT in the lung and bladder 23 is well known, however, and even in a wide range of anatomical sites examined, there is a low rate of local recurrence (25%) and no metastases reported (Table 3). 2,10,15 This indicates that vesical IMFT may be treated with conservative surgical excision compared to that performed with sarcomatous lesions, which may resemble IMFT clinically and radiologically.…”
mentioning
confidence: 99%